Angela Wagoner, Book Cart Volunteer - (:unkn) unknown (Coy C. Carpenter Library, 1989)
Published in: Synapse. 1989.
In 1949, the Bowman Gray School of Medicine Guild began a bookmobile operation. The Guild's members were the wives of doctors and medical school officials. The book mobile regularly circulated among the patients providing them with books and magazines. The bookmobile volunteers covered the second, third and fifth floors of the then five-story North Carolina Baptist Hospital. Shown here is a teen volunteer, Angela Wagoner, doing the same thing 40 years later in 1989. She was a summer "teen volunteer" who helped filled a need of the staff shortage at North Carolina Baptist Hospital during the summer vacation months. The summer Volunteen program, which is for teenagers between the ages of 14-18, have to commit to two days of volunteering per week from 9am-4pm in order to be eligible. The program was and still is today in 2007, a good way to expose teenagers to a medical center environment and the career opportunities that are available to them.
Keywords: Forsyth County (N.C.) -- History -- Pictorial works; Forsyth County (N.C.) -- History -- Sources; Digital Forsyth